NEW FINDINGS NOTES OF THE PARASITIC NEMATODES OF TERRESTRIAL INVERTEBRATES IN VIET NAM - Pham Van Luc; Nguyen Vu Thanh; S.E. Spiridonov (Universitas Gadjah Mada, 2008)
First results of the parasitological survey of Vietnamese terrestrial invertebrates performed in 2007 demonstrate extreme diversity of nematodes parasitic in these animals. The most interesting new findings are nematodes of four superfamilies: Drilonematoidea, Thelastomatoidea, Rhabditoidea and Ransomnematoidea. Further progress was achieved in last three years in the studies of Drilonematoidea nematodes – coelomic parasites of earthworms. One new genus and several new species were discovered in large megascolecids collected in Bac Bo (Tam Dao) and Nam Bo (Bidoup - Nui Ba N.P.). Passalidae beetles are colonial coleopterans inhabiting rotten wood in tropical forests throughout tropics, and are known as characteristic hosts of one taxon of parasitic nematodes – family Hystrignathidae. The nematodes of this family were reported for the first time from Viet Nam in 2007. The fauna of parasitic nematodes of terrestrial mollusks is also diverse in Viet Nam. In addition to the new angiostomatids described in 2005 new Angiostoma species with unusual morphology was discovered in Cat Tien National Park. Nematodes of the family Hethidae were discovered in Vietnamese diplopods in 1997 but not identified up to species level. Examination of Heth specimens under light microscope and scanning electron microscope demonstrate prominent morphological differences between three samples from different areas in Viet Nam. Additional studies are needed to reveal the relationships of parasitic nematodes of terrestrial invertebrates found in Vietnam in 2007 and publish valid descriptions of these new taxa.